Method of vibration diagnostics of pre-emergency conditions in technogenic and natural objects - A.V. Grigoryev (Известия высших учебных заведений. Поволжский регион:Технические науки, 2024)
Background. The purpose of the study is to develop a method for measuring vibrations based on the analysis of images of a round-shaped test fragment with vibration blur by measuring the direction of vibration of the surface element of the test object. The relevance of the purpose is due to the increase in the information content of vibration monitoring, which can significantly reduce the likelihood of missing pre-emergency conditions. Materials and methods. Studies of the process of vibration blurring of the image of an object’s test fragment and restoration of the trajectory of vibrational movement based on analysis of the image of a test fragment with vibration blur were carried out using the method of mathematical modeling. Results. A substantive analysis of the state of the issue of measuring vibration parameters was carried out based on an image analysis of a round test fragment. An approximate block diagram of an information-measuring system for vibration diagnostics of pre-emergency states of objects is given. A description of the processes of formation and processing of information video streams carried out at the output of the recording device of the IIS is given. A generalized description of the principles of forming tuples of geometric parameters of images of a test fragment is given. A description of the principles for restoring vibration parameters and identifying pre-emergency states of objects is given. The tasks and principles of calibration measurements of the IMS and the choice of a standard measuring device used for such measurements are substantiated. It is noted that the proposed method makes it possible to measure vibration parameters in a significantly wider frequency range compared to a standard vibrometer and other known vibrometry methods. In addition, the proposed system, unlike the standard vibrometer and other vibration measuring systems, is capable of analyzing vibrations along an arbitrary trajectory. Conclusions. A method for identifying pre-emergency states of man-made and natural objects is presented. An approximate block diagram of the IMS that implements this method is presented and described. The expansion of the functionality of this IMS in comparison with known vibration measuring systems is justified.